2018
DOI: 10.1111/lsi.12317
|View full text |Cite
|
Sign up to set email alerts
|

Summonsing Criminal Desistance: Convicted Felons' Perspectives on Jury Service

Abstract: This exploratory study is the first to examine how convicted felons view the jury process and their role in that process. Data derived from interviews with former and prospective felon‐jurors in Maine, the only US jurisdiction that does not restrict a convicted felon's opportunity to serve as a juror, reveal that participants displayed an idealized view of jury service, stressing a commitment to serve conscientiously. Additionally, inclusion in the jury process affirmed their transitions from “offenders” to “n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…For many, convicted felons' supposed criminal loyalties and presumed collective hatred for the state makes felon-juror exclusion "feel" logical, and perhaps even inevitable. However, recent studies not only show that the presumed bias of convicted felons is dramatically overstated (Binnall, 2014) and that the character of citizens with a felony criminal conviction does not diminish their fitness for jury service (Binnall, 2018a), but that felon-juror inclusion might, in fact, add to deliberation quality and help facilitate successful reintegration/criminal desistance (Binnall, 2019(Binnall, , 2018b(Binnall, , 2018c.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For many, convicted felons' supposed criminal loyalties and presumed collective hatred for the state makes felon-juror exclusion "feel" logical, and perhaps even inevitable. However, recent studies not only show that the presumed bias of convicted felons is dramatically overstated (Binnall, 2014) and that the character of citizens with a felony criminal conviction does not diminish their fitness for jury service (Binnall, 2018a), but that felon-juror inclusion might, in fact, add to deliberation quality and help facilitate successful reintegration/criminal desistance (Binnall, 2019(Binnall, , 2018b(Binnall, , 2018c.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the exclusion of convicted felons from jury service has received considerably less scholarly attention (Binnall, 2009), with only a handful of studies examining the topic to date (for a review, see Binnall, 2019). Those few studies demonstrate that, like felon-voter disenfranchisement, felon-juror exclusion racially homogenizes a democratic institution (Wheelock, 2011), rests on tenuous justifications (Binnall, 2014), might negatively influence the reintegration of former offenders (Binnall, 2018a;2018b), and can promote the "othering" of citizens with a felony criminal record (Binnall, 2018c). Given this lack of attention, felon-juror exclusion stands as arguably "the last acceptable form of civic banishment" (Binnall, 2010, pp.…”
Section: Introductionmentioning
confidence: 99%
“…Stigmas are attributes that cause someone to be discarded and no longer accepted by others—a judgment on an individual’s character (Goffman, 1963). Stigma can lead to a negative sense of self, which influences interactions with others (Binnall, 2018; Copenhaver, Edwards-Willy, & Byers, 2007). One study finds that answering a question around a conviction history on a college application decreases the likelihood of completion for persons with conviction histories (Custer, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In his research on disenfranchisement, Binnall (2018) found that people with conviction histories become self-conscious of the “felon” label, leading them to worry about how others will view and interact with them. The mental awareness of being considered and labeled a “felon” can negatively influence people with conviction histories that could thus decrease their sense of community and connection on college campuses (Ott & McTier, 2019), thereby reducing the likelihood of college persistence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yet every state except for Maine and Colorado limits jury participation for those convicted of felonies in some way, and twenty-eight states impose complete bans. 331 Thirteen states disqualify at least some potential jurors based on misdemeanor convictions. 332 The sole empirical study examining the pretrial biases of this group, however, reveals that levels of pro-defense and anti-…”
Section: Michigan Law Reviewmentioning
confidence: 99%